Implementasi Pendidikan Karakter pada Siswa SMP - Medi Yansyah; Hesti Hesti; Mardiana Mardiana; Musiman Musiman (Journal on Education, 2023)
It is claimed that degradation moral happens to our young generation lately. Their behavior does not reflect the good conduct of our nation. This study is done to describe the characteristics of an ideal visioner leader and to describe the process of character education in school. Using qualitative etnografy approach, the writer explored various references to draw the conclusion. The ideal visioner leader is: a) having future insight, b) willing to take action to reach the goal, c) able to influence other people, d) able to formulate vision, e) able to realize vision inti action, f) commit to spiritual values, g) develop the relationship, h) innovative. The process of character education is integrated in all the scholl subjects and in other school activities.